PRESCRIPTIVE AND PROSCRIPTIVE FEMALE GENDER ROLE PROVERBS IN TONY UCHENNA UBESIE’S ISI AKWU DARA N’ALA i - Mba, Mary (Proverbium - Yearbook, 2015)
Traditionally, the Igbo culture is remarkable for its prescriptive and proscriptive gender stereotypes for women. Most of the time, if a woman does not subscribe to these gender roles, she is considered a bad woman and sometimes, ostracized. In this paper, I look at prescriptive and proscriptive gender role proverbs in Tony Ubesie’s novel, Isi Akwu Dara N’Ala. I show that Tony Ubesie’s work, though fictional, is grounded in the Igbo culture, as Ubesie bases his story on Igbo oral proverbs that portray Igbo traditions. In doing so I argue that Isi Akwu Dara n’Ala is more of a propaganda designed to prescribe and pro-scribe gender roles to Igbo women, who found freedom and independence, due to their roles as sole providers for their families during the Nigerian-Biafran Civil War. The novel is therefore an attempt to re-subjugate Igbo women to Igbo men after the war.